Risk Coping Strategies among Chinese Breast Cancer Survivors: A Qualitative Study - Dong, Ruishu; Aun, Nur Saadah Mohamad; Amin, Aizan Sofia; Hassan, Nazirah (Journal of Ecohumanism, 2024)
Breast cancer (BC) is intricately linked with emotions, underscoring the importance of BC survivors adopting effective coping strategies. This study utilized qualitative research methods and semi-structured interviews to explore the evolving coping strategies of 15 Chinese BC survivors throughout their recovery journey. Through the process of coding and organizing the interview data, it was found that individuals frequently shifted from employing negative coping strategies to employing active coping strategies when faced with risk. The transformation approaches include from ineffective emotional venting to positive reappraisal; from focused on thought/rumination to avoidance; from putting into perspective to positive focusing; from other blame to positive refocusing; identifying and cleaning up irrational emotions; self-awareness growth. Furthermore, three coping strategies emerged: emotion-focused coping; problem-focused coping; and meaning-focused coping. Each coping strategy offers unique strengths and appropriate situations. The findings underscore the importance of fostering a positive outlook on risks among BC survivors and continuously enhancing their coping skills to navigate the challenges they encounter.